Resection or Ablation for Early Hepatobiliary Carcinoma: A Meta-Analysis of Treatment Outcomes - Jamaludin; Hengky Setyahadi (Surgery Department, Faculty of Medicine Universitas Sriwijaya, 2024)
Introduction: The optimal treatment for early hepatobiliary carcinoma (EHBC) remains controversial, with surgical resection and ablation offering distinct advantages and disadvantages. This meta-analysis aimed to compare the long-term outcomes of these two modalities in patients with EHBC. Methods: A systematic search of PubMed, Scopus, and Google Scholar was conducted for studies published between 2018 and 2024 that reported on the outcomes of resection or ablation in EHBC. The primary outcomes were overall survival (OS) and recurrence-free survival (RFS). The secondary outcomes included complication rates and length of hospital stay. Results: A total of 25 studies (n=4,512 patients) were included in the meta-analysis. The pooled analysis showed that resection was associated with significantly better OS (HR 0.62, 95% CI 0.51-0.75, p<0.001) and RFS (HR 0.58, 95% CI 0.47-0.71, p<0.001) compared to ablation. However, resection was also associated with a higher risk of complications (OR 1.83, 95% CI 1.32-2.54, p<0.001) and a longer hospital stay (MD 3.2 days, 95% CI 2.1-4.3, p<0.001). Conclusion: Resection offers superior long-term oncological outcomes compared to ablation in patients with EHBC. However, the choice of treatment should be individualized based on patient factors and tumor characteristics, considering the higher risk of complications and longer hospital stay associated with resection.